(untitled) (Research, Society and Development, 2024)
In recent years, the transmission of Trypanosoma cruzi has intensified, due to the growth of oral infections, more specifically in Latin American countries. This type of contagion is related to the development of Acute Chagas disease (ACD). From this perspective, an integrative review was conducted, which was carried out through the analysis of articles published in the Pubmed, LILACS, Scopus and Embase databases. From the establishment of inclusion and exclusion criteria, 17 results were selected from 422 articles found to construct this scientific material. Although vector transmission of Trypanosoma cruzi trypomastigotes has attenuated in Latin America, oral infections have silently spread over the years. In this scenario, several epidemiological surveillance actions have already been adopted by countries, however, some aspects related to the increase in ACD still need to be clarified. Therefore, the objective of this article is to analyze which factors trigger the increase in oral infections by Trypanosoma cruzi.